2018
DOI: 10.1002/ame2.12024
|View full text |Cite
|
Sign up to set email alerts
|

Vibration in mice: A review of comparative effects and use in translational research

Abstract: Sound pressure waves surround individuals in everyday life and are perceived by animals and humans primarily through sound or vibration. When sound pressure waves traverse through a solid medium, vibration will result. Vibration has long been considered an unwanted variable in animal research and may confound scientific endeavors using animals. Understanding the characteristics of vibration is required to determine whether effects in animals are likely to be therapeutic or result in adverse biological effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Previous studies have used vibration frequencies of approximately 47 or 50 Hz to demonstrate that LLFV at 50 Hz contributes to vasodilation and wound healing 11–13,18 . However, the chosen frequency was based on preliminary considerations, and other studies have also shown blood flow enhancement effects at different vibration frequencies 26–28 . Therefore, further investigations are needed to explore the vibration frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used vibration frequencies of approximately 47 or 50 Hz to demonstrate that LLFV at 50 Hz contributes to vasodilation and wound healing 11–13,18 . However, the chosen frequency was based on preliminary considerations, and other studies have also shown blood flow enhancement effects at different vibration frequencies 26–28 . Therefore, further investigations are needed to explore the vibration frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13]18 However, the chosen frequency was based on preliminary considerations, and other studies have also shown blood flow enhancement effects at different vibration frequencies. [26][27][28] Therefore, further investigations are needed to explore the vibration frequency. Regarding vibration intensity, our previous study involved applying LLFV to the ears of non-diabetic mice, revealing that blood flow promotion varied depending on intensity.…”
Section: Improvement In Inflammation and Alteration Of Macrophage Phe...mentioning
confidence: 99%
“…However, there is a common misconception about the inaudibility of infrasound since sounds with lower frequencies can still be heard with an increase of the sound pressure level [ 24 , 26 ]. Higher pressure levels, as the ones used in our study, can elicit both body vibration and hearing response from the animal model used [ 32 , 33 ]. As such, we cannot exclude animal stress due to audible noise with subsequent activation of the neuroendocrine pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Rs") principle is adopted, efficacy of new medical device or novel therapeutic is assessed in animals prior to clinical use in humans [1]. However, success rate of most therapeutics during clinical trial in human remain low [2].…”
mentioning
confidence: 99%
“…Diverse array of studies implicated migration in human as a precipitating factor for mental illnesses [7], metabolic related disorders in children [8] and other forms of health deteriorations depending on the stressors experienced before, during and after changing the environment [9]. Because human and animals share similar organ systems, and many therapeutics or diseases showed similar expressions in them [1], there is a possibility that longterm cage-to-cage migration of experimental animals could trigger similar stressors-induced changes for certain health indices. This likelihood is further fortified by the fact that environment is a critical stressor for all species and any form of environmental change may have a consequential effect on health [9].…”
mentioning
confidence: 99%